2004
DOI: 10.1136/bmj.38184.606169.ae
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase type B inhibitors in early Parkinson's disease: meta-analysis of 17 randomised trials involving 3525 patients

Abstract: Objective To quantify more reliably the benefits and risks of monoamine oxidase type B inhibitors (MAOBIs) in early Parkinson's disease. Data sources Searches of the Cochrane Library, Medline, Embase, PubMed, and Web of Science for years 1966-2003, plus major journals in the field, abstract books, and proceedings of meetings, for randomised trials comparing MAOBIs with placebo or levodopa. Data extraction Available data on mortality, motor complications, side effects, treatment compliance, and clinician rated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(83 citation statements)
references
References 34 publications
3
72
0
8
Order By: Relevance
“…The clinical benefit of selegiline is relatively mild, with most studies showing a total UPDRS improvement of 2.7 points at 3 months. 70 In a long-term follow-up study of the DATATOP cohort, L-dopa-treated patients who were originally randomized to selegiline had significantly less decline, with less wearing off, on-off, and freezing episodes. 71 Similar benefits of early selegiline treatment together with re-duced L-dopa dose requirements were observed in the long-term Nordic study.…”
Section: Monoamine Oxidase B Inhibitorsmentioning
confidence: 98%
“…The clinical benefit of selegiline is relatively mild, with most studies showing a total UPDRS improvement of 2.7 points at 3 months. 70 In a long-term follow-up study of the DATATOP cohort, L-dopa-treated patients who were originally randomized to selegiline had significantly less decline, with less wearing off, on-off, and freezing episodes. 71 Similar benefits of early selegiline treatment together with re-duced L-dopa dose requirements were observed in the long-term Nordic study.…”
Section: Monoamine Oxidase B Inhibitorsmentioning
confidence: 98%
“…A systematic review of monoamine oxidase B inhibitor symptomatic therapy trials [12] showed a similar positive effect of an initial policy of MAOBI therapy with a reduction in motor fluctuations of 25% (Fig. 7).…”
Section: Symptom Controlmentioning
confidence: 80%
“…Consequently, PD patients are mainly diagnosed based on symptoms, with neuroimaging tests such as the DA-based PET imaging being used for confirmation, although its high cost precludes its routine use in the clinic 47 . No cure for PD is presently available; however, several MAO-B inhibitors have been shown to provide relief from the symptoms and are currently being used for the treatment of early-stage PD [11][12][13] . The biological and clinical importance of MAO-B in PD has led us to successfully develop U1, a first-generation, two-photon fluorogenic imaging probe.…”
Section: Discussionmentioning
confidence: 99%
“…In PD patients, the elevation in MAO-B activity causes highly membrane-permeable H 2 O 2 generated to diffuse from astrocytes to neighbouring neuronal cells, which consequently leads to oxidative stress and their eventual degeneration. Notably, both selegiline and rasagiline are FDAapproved drugs for the treatment of early-stage PD, and they work by selectively inhibiting overexpressed MAO-B activity in the patients [11][12][13] . MAO-A-selective inhibitors such as clorgyline, however, are devoid of such therapeutic effects.…”
mentioning
confidence: 99%